Some Remarks on Fibrations in Complex Geometry (Journal of Mathematical Study, 2025)
In this article, we discuss some properties of holomorphic fibrations in the complex analytic setting.
Keywords: Holomorpic fibration; discriminant locus; monodromy representation; rational tree singularities; conic bundles; Leray spectral sequence